ПІДВИЩЕННЯ ККД БАГАТОФАЗНОЇ СИСТЕМИ ЖИВЛЕННЯ ІЗ ЗАСТОСУВАННЯМ ЕНЕРГОЕФЕКТИВНИХ СТРАТЕГІЙ ПАРАЛЕЛЬНОЇ АКТИВНОЇ ФІЛЬТРАЦІЇ - Артеменко, М.Ю.; Чопик, В.В.; Михальський, В.М.; Шаповал, І.А.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2022)
Minimizing energy losses and increasing the efficiency of a multiphase power supply system by increasing the load power factor using an active shunt filter (SAF) is analyzed. Two SAF control strategies are presented, which provide the maximum efficiency at close to the unit value of power factor or at sinusoidal symmetric currents of the power supply system with any number of phases for non-sinusoidal and asymmetric sources, nonlinear and asymmetric load, and the arbitrary ratio of the resistance of linear and neutral wires. It is shown that the use of direct information about the EMF of a multiphase source as a reference vector of the desired transmission line current does not improve the achieved result of efficiency maximization. A virtual experiment obtained and verified the formula for calculating the efficiency of a multiphase power supply system with an arbitrary load in the form of dependence on load factor and power factor. The power supply system's power factor was determined and experimentally confirmed when applying the SAF strategy to form sinusoidal symmetric currents of a multiphase source. References 10, figures 5.